P106/O25 DNA methylation in lymphocyte subsets as a mediator of genetic risk in early rheumatoid arthritis. (March 2019) - Clark, AD; Nair, N; Skelton, AJ; Anderson, AE; Thalayasingam, N; Naamane, N; Diboll, J; Massey, J; Eyre, S; Barton, A; Isaacs, JD; Reynard, LN; et al.
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Genome-wide association studies (GWAS) have identified over 100 RA-associated risk loci, whose enrichment for lymphocyte-specific enhancer elements is consistent with a regulatory function of many causal variants in these cells. Epigenetic modifications have also been strongly implicated in RA pathogenesis. Objectives: To investigate the role of DNA methylation as a mediator of RA genetic risk. Methods: CD4+ T lymphocyte-specific DNA and RNA were extracted from freshly isolated blood of 43 RA and 60 disease control patients, along with equivalent material from B-lymphocytes of 46 RA and 73 controls. Comparator groups were drug-naïve and matched for age, sex, and acute phase response. Genotyping, gene expression and methylation profiling was carried out using Illumina chip array technology. After mapping genome-wide methylation quantitative trait loci (mQTLs) in cis (<1 Mb), we focused on known RA risk loci, integrating paired normalised gene expression measurements for transcripts within 500 kb of index CpGs. We also sought trans mQTLs, highlighting RA-specific effects. Results: CD4+ T lymphocyte cis -mQTLs co-localised with 30 independent (r2<0.8) RA-associated SNPs, whilst in B lymphocytes such mQTL effects were present at 31 RA SNPs. 80% of these variants functioned as cis -mQTLs in both cell types. CpG sites subject to cis effects at risk loci were depleted in regions associated with cell type-specific repressed chromatin marks, with enrichment at enhancer regions and those flanking transcription start sites, suggesting active roles in transcriptional regulation. Linear regression identified regulatory effects of these CpG sites on gene expression, and causal inference testing highlighted genes for which risk SNPs most likely modulate gene expression via CpG methylation. Such effects, robust to false discovery rate, were particularly prevalent in CD4+ T lymphocytes, for example implicating ANKRD55, ORMDL3, and FCRL3 as causal genes in this cell type. Our analysis of mQTLs acting in trans identified inter-chromosomal SNP-CpG associations, also revealing instances of differential effect size in RA patients and controls. Conclusions: Here we highlight an important mechanism by which genetic variants may contribute to altered lymphocyte phenotype, and demonstrate the utility of DNA methylation profiling as a tool for the prioritization of candidate genes following GWAS studies in RA. The functional roles of highlighted genes in CD4+ T cells during RA pathogenesis await clarification. Disclosure of Interest: None declared.